2018
DOI: 10.1038/s41388-018-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying BRAF alterations in cancer: new rational therapeutic strategies for actionable mutations

Abstract: The RAS-RAF-MEK-ERK signaling cascade is among the most frequently mutated pathways in human cancer. Approximately 50% of melanoma patients possess a druggable hotspot V600E/K mutation in the BRAF protein kinase. FDA-approved combination therapies of BRAF and MEK inhibitors are available that provide survival benefits to patients with a BRAF V600 mutation. Non-V600 BRAF mutants are found in many cancers, and are more prevalent than V600 mutations in certain tumor types. For example, between 50-80% of BRAF muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
423
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(441 citation statements)
references
References 144 publications
9
423
3
6
Order By: Relevance
“…Mutations generating class 2 (eg K601E, G469A and F595L) or class 3 (eg G469E) mutants have also been described in iCCA . Class 2 and class 3 mutants are oncogenic, but insensitive to currently available BRAF inhibitors . Regardless of the structural bases underpinning their signalling activity, all classes of BRAF mutants drive cell transformation through activation of the MEK/ERK module, which creates the opportunity of interfering with their activity through MEK1/2 blockade .…”
Section: Molecular Signalling Mapmentioning
confidence: 99%
“…Mutations generating class 2 (eg K601E, G469A and F595L) or class 3 (eg G469E) mutants have also been described in iCCA . Class 2 and class 3 mutants are oncogenic, but insensitive to currently available BRAF inhibitors . Regardless of the structural bases underpinning their signalling activity, all classes of BRAF mutants drive cell transformation through activation of the MEK/ERK module, which creates the opportunity of interfering with their activity through MEK1/2 blockade .…”
Section: Molecular Signalling Mapmentioning
confidence: 99%
“…The Class I, BRAF Val 600 , variants are uncommon in RASopathies (Li et al, ), but non‐Val 600 Class II and Class III BRAF variants are observed in CFC. Class II BRAF variants function as RAS‐independent constitutively active dimers, while Class III BRAF variants increase MAPK signaling due to an increased ability to be activated by RAS (Dankner, Rose, Rajkumar, Siegel, & Watson, ). The RAF family member RAF1 is rarely mutated in cancer, but germline pathogenic variants in RAF1 are found in individuals with NS (Pandit et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, they are identifying more patients whose tumors express non-V600 BRAF mutations. Until recently, the prognostic and therapeutic relevance of these mutations was poorly understood (2). Dagogo-Jack and colleagues have published the largest and most comprehensive clinical dataset to date, derived from patients with BRAF-mutant NSCLC, including both non-V600 (class 2 and 3) and V600 (class 1) mutations.…”
mentioning
confidence: 99%
“…There is now a growing body of evidence demonstrating that class 2/3 BRAF mutations are associated with an aggressive clinical course in NSCLC and melanoma (1)(2)(3). These are actionable mutations and effective targeted therapies are thus warranted.…”
mentioning
confidence: 99%